Antioxidant properties of chemical extracts and bioaccessible fractions obtained from six Spanish monovarietal extra virgin olive oils: Assays in Caco-2 cells. Issue 7 (8th July 2015) - Borges, Thays H.; Cabrera-Vique, Carmen; Seiquer, Isabel
<x xml:space="preserve">Abstract</x> The antioxidant activity and the total phenolic content of six Spanish commercial monovarietal extra virgin olive oils were evaluated in chemical extracts and in bioaccessible fractions obtained after in vitro digestion.